A cultural evaluation of the causes and treatment of diseases and other misfortunes among communities in the Pietersburg and Mankweng areas of the Northern Province - Mabunda, Michael Mucheyeni. (University of Limpopo, 1999)
Refer to document
Thesis (M.A.(Anthropology)) --University of Limpopo, 1999
Keywords: Deseases; Treatment of diseases; Diagnosis; Diseases control; Symptomatology; Disease tramsmission